Diffusion-reaction of substrate in cylindrical immobilized bio-catalyst - Jameel, Ahmed Tariq; R Muhamad Fakih, RM Syibli Milasi (IIUM Press, 2011)
The mass transfer effect on the overall reaction rate in a cylindrical immobilized biocatalyst has been investigated theoretically. Zero order and first order kinetics were taken into consideration. The mass balance for the substrate on a cylindrical shaped biocatalyst results into an ordinary differential equation (ODE) which can be solved numerically and/or analytically using appropnate boundary conditions. Detailed steps for analytical solutions are presented for zero and first order kinetics. The differential equation for zero and first order kinetics was changed into a dimensionless form by defining suitable dimensionless variables. The concentration profiles inside the porous biocatalyst were obtained as a function of Thiele modulus.